Receiving abortion services at nongovernmental health facilities as a significant variable for postabortion family planning utilization: a comparative cross-sectional studyAJOG Global Reports at a Glance - Mewujidat H. Ali, MPH; Mezgebu Y. Mengistu, PhD; Zinet Abegaz, MPH; Getaw W. Bazie, MPH; Niguss Cherie, MPH; Erkihun T. Amsalu, MPH (Elsevier, 2022)
BACKGROUND: Postabortion family planning is a major primary prevention strategy for unwanted pregnancies at which contraceptive use reduces approximately 230 million births every year worldwide. However, evidence that assesses postabortion family planning utilization and associated factors among women who received abortion services at governmental and nongovernmental health facilities is limited. OBJECTIVE: This study aimed to compare the rates of postabortion family planning utilization and associated factors among women who received abortion services at governmental and nongovernmental health facilities. STUDY DESIGN: A comparative cross-sectional study design was employed among 324 women who received abortion services. A systematic sampling technique was used to select the study participants, and data were collected by face-to-face interview using a structured questionnaire. Data were cross-checked, coded, and entered into EpiData (version 3.1; The EpiData Association, Odense, Denmark) and exported to Statistical Package for Social Sciences (version 25; IBM Corp, Armonk, NY) for analysis. Descriptive statistics, such as frequency, proportion, and mean with standard deviation, were computed. The association between independent variables and postabortion family planning utilization was made using a binary logistic regression model. Adjusted odds ratio with its 95% confidence interval was used as a measure of association, and variables with a P value of ≤.05 were considered significant. RESULTS: The rate of postabortion family planning utilization among women who received abortion services was 71.91% (95% confidence interval, 66.74-76.56). The rates of postabortion family planning utilization at governmental and nongovernmental health facilities were 55.6% (95% confidence interval, 47.75-63.10) and 88.27% (95% confidence interval, 82.27-92.43) respectively. Being counseled about contraceptive use (adjusted odds ratio, 33.130; 95% confidence interval, 6.089-180.243), not needing near-future pregnancy (adjusted odds ratio, 3.350; 95% confidence interval, 1.541-7.282), and receiving abortion service at nongovernmental health facilities (adjusted odds ratio, 4.732; 95% confidence interval, 1.900-11.787) were significantly associated with postabortion family planning utilization. CONCLUSION: The rate of postabortion family planning utilization was lower among women who received abortion services at governmental health facilities than among women who received abortion services at nongovernmental health facilities. Counseling about contraceptive use, need for near-future pregnancy, and type of health facility were significantly associated with postabortion family planning utilization. Therefore, efforts are needed to promote and strengthen the counseling of contraceptive use and birth spacing of women who are receiving abortion services.